Applying Shared-Parking Turn-Time (SPaTT) model and geographic information system in the supply and demand analysis of parking space - Mar Iman, Abdul Hamid (CRES, FKSG, 2006)

(untitled)
Parking space is a basic and important public facility in urban areas. Problems of parking space are said to be always occuring in urban areas, especially in the city centre or busy commercial and services zones. In Malaysia, the common parking system adopted is shared-parking turn-time system, whereby members of the public share limited parking space in the city centre and have to take turns to keep their vehicle temporarily in parking lots. City centres are said to be suffering from insufficient parking space, forcing people to park their vehicles on road shoulders or outside the gazetted parking lots. This causes traffic congestion and arouses question of sufficiency of parking space in such areas. The basic task in addressing this issue is by carrying out supply and demand analysis of parking space. The objective of this study is to apply a spatial technique using the Geographic Information System (CIS) in modelling the supply and demand of parking space, taking Johor Bahru city centre as a study case. Maps of buildings, land cadastre, urban land use, and others such as road and street networks are digitally constructed to form a spatial database of supply and demand of parking space in the study area. Attribute data on building inventory, building characteristics, land use, space supply, and demand of parking space are obtained from the Johor Bahru City Council, private parking companies operating in the city, observational, as well as interview surveys in the study area. The shared-parking turn-time model - the "SpaTT model" - is developed to analyse spatial distribution of parking space supply and demand in the study area. The "SpaTT model" is then incorporated into Arc View 3.1 to determine parking space equilibrium across the study area. This, in turn, is used to determine zones with parking space deficit and, thus, which need additional parking lots. The study discloses that there is reasonable level of parking space equilibrium in the study area. In other words, there is no evidence of acute supply problem of parking space in the Johor Bahru city centre as perceived, although there are zones where additional on-street parking could be provided to add parking supply.